PENINGKATAN KOMPETENSI PROFESIONAL GURU DALAM PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS ICT DI UPT SD NEGERI WONODADI 01 KECAMATAN WONODADI - Mahdisom; Isna Nurul Inayati (Universitas Islam Raden Rahmat Malang, 2022)
The Covid-19 pandemic has changed the way people live. This includes the need for technology. This condition certainly needs special attention from schools. Especially in monitoring and improving teacher competence in using ICT-based learning media. The results of observations made at the UPT SD Negeri Wonodadi 01 are known that the majority of teachers do not use ICT-based learning media when teaching because they experience difficulties in developing media and they have the assumption that the development of ICT-based learning media is expensive. So to improve the teaching and learning process, school action research through the development of ICT-based learning media in schools needs to be carried out. This type of research is school action research, this research was carried out at SD Negeri Wonodadi 01 in November 2021 with the research subjects being all 10 teachers of SD Negeri Wonodadi 01. The technique of collecting data from this school action research is through qualitative data obtained from observations, interviews and document studies. This procedure includes the following stages: (1) planning, (2) implementation, (3) observation, and (4) reflection. The results showed that in general the quality of the implementation of the activities had increased and the impact of the activities had a positive effect on student well-being. It was concluded that the professional competence of teachers in the development of ICT-based learning media increased.